Evidence of sensory error threshold in triggering locomotor adaptations in humans - Emily M. Herrick; Sergiy Yakovenko (PLoS ONE, 2025)
Changing body biomechanics or external conditions trigger neural adaptations to optimize motor behavior. While the adaptations appear to be constantly minimizing movement errors, not all errors necessarily initiate sensorimotor adaptations. The locomotor control system may resist changes since exploratory modifications can lead to critical failures in walking. Theoretically, this implies the presence of an error threshold to trigger the adaptation mechanism. Here, kinematic and kinetic asymmetries were imposed as conditions on stepping using a passive orthosis (kinematic asymmetry) and real-time feedback about limb loading (kinetic asymmetry) to vary sensorimotor error during locomotion on a treadmill. Healthy participants adapted to asymmetric conditions while walking on a tied-belt treadmill. The asymmetry in leading and trailing double stance captured the presence of aftereffects, and consequently adaptation, in two conditions: i) only kinematic constraints, or ii) kinematic and kinetic constraints. We tested the hypothesis that the presence of adaptation depends on the magnitude of locomotor asymmetry. Kinematic asymmetry alone did not induce persistent locomotor adaptation; however, the addition of asymmetric interlimb loading triggered the expected adaptation. This result suggests that uninjured locomotor systems can cope with a range of kinematic asymmetries without initiating persistent adaptations, and that loading may be a key variable for triggering the adaptation. The error threshold within the adaptation mechanism may mitigate possible disruption of locomotion when adaptation is not necessary. These insights elucidate the mechanism of neural plasticity and have implications for rehabilitation.